A Robust Strategy for Sustainable Organic Chemicals Utilizing Bioprivileged Molecules. Issue 13 (9th April 2019) - Shanks, Brent H.; Broadbelt, Linda J.
Abstract: Biobased chemicals will inevitably be an important part of a sustainable organic chemical industry. Current efforts in biobased chemicals are largely driven by opportunistic chemical product targets requiring complete technology development from feedstock to final product for a specific molecule. To enhance the development of biobased chemicals, it is important to create strategies that can be more systematic and can leverage advancements across multiple final products. Discussed here is the concept of bioprivileged molecules, which are chemical intermediates that have the potential to be efficiently converted into a range of product molecules that can both directly replace existing petrochemicals and are novel molecules that impart enhanced performance properties in end‐use applications. Abstract : Bioprivileged Molecules : A concept for the systematic development of a sustainable organic chemical industry that replaces petrochemicals and introduces new chemical products is discussed.